Analysis of Moment of the Truth in Public Services Improvement in Semarang Regency - herbasuki nurcahyanto; Aufarul Marom (Dialogue : Jurnal Ilmu Administrasi Publik, 2022)
Moment of the truth is one approach that can be used to improve public services. It represents the interaction between users and providers in service.  The user will give an assessment on the provider’s services during the interaction. In addition, the users who have good memory during the interaction with the organizer will give a positive assessment to the provider. This research aims to analyze the interaction between users and providers of the One-Stop Integrated Investment and Licensing Service Office (DPMPTSP) of Semarang regency. This study used descriptive analytical method with a qualitative approach. The results showed that officers were responsive, communicative and friendly to customers. Officers also assisted users who found any difficulty in the online licensing process. Users hoped that the communication way can be maintained and even improved. The perceived obstacle was the duration of the service process especially that related to the services provided by the technical service.  To overcome these obstacles, leadership-level coordination is required so that services can be provided according to the determined time standards and this encourages the establishment of public service malls that can integrate various technical services in one service provider unit.